Pharmacophore Screening and Molecular Docking of Andrographolide and Its Derivatives on Plasmepsin as Antimalarial Drug - Sandra Megantara (Journal of Global Pharma Technology, 2020)
The study was conducted to find out andrographolide and its derivatives which could interact with plasmepsin, an aspartic protease enzyme that usually used as target for antimalaria. The study began with pharmacophore modeling using LigandScout software. Pharmacophores were searched for plasmepsin I, II, and IV, with pdb codes were 3QS1, 1SME, and 1LS5 respectively. Pharmacophores were generated using structure-based and ligand-based pharmacophore methods and retrospective validation was used to validate them. Pharmacophore screening was carried out for andrographolide and its derivatives, then for the hit compounds, continued by molecular docking using AutoDock Vina module in LigandScout software. Pharmacophores for plasmepsin I, II, and IV consist of hydrogen bond donors, hydrogen bond acceptors and hydrophobic interactions, with the best validated AUC values for each model were 0.73, 1.00, and 1.00 respectively. Andrographolide derivatives (AND10 and AND15) had high fit scores for plasmepsin I, II, and IV pharmacophore. The results of molecular docking showed that andrographolide and its derivatives (AND10 and AND15) interacted well with the plasmepsin by binding to important aspartic amino acid residues in the active site. From the binding affinity, AND15 was the best compound interacted with plasmepsin I, II, and IV with ∆G values were 1, 2, and 3 kcal/mol respectively. Andrographolide derivative (AND15) was the best compound interacted with plasmepsin, so it was potential to be developed into new antimalarial drug.